Pengaruh Pemberian Specific Footwork Training Terhadap Agility Pada Pemain Basket Di Sman 1 Kartasura - Achsanuddin, Nur Rahmah Zuraida, Dwi Kurniawati, SSt.FT., M.Kes (2017)
ABSTRACT STUDY PROGRAM S1 PHYSIOTHERAPY FACULTY OF HEALTH SCIENCE UNIVERSITY MUHAMMADIYAH OF SURAKARTA NUR RAHMAH ZURAIDA ACHSANUDDIN / J 120 151 092 "EFFECT OF SPECIFIC FOOTWORK TRAINING FOR AGILITY ON BASKETBALL PLAYERS IN SMAN 1 KARTASURA" Background: Agility has a really great role in basketball, it is because agility is one of the basic skills that must be possessed in this game. The techniques in basketball game requires speed, strength, coordination / balance, and a good flexibility, and all the components are present in agility itself. Agility exercises can improve the speed, reaction time, balance and coordination. Many exercises that can be used in an effort to improve one's agility, one of them by using footwork training. Objective: To determine whether there is influence of a specific footwork training for agility on basketball players in SMAN 1 Kartasura Method: This type of research is a kind of quasi experimental approach, the research by conducting experiments to determine the symptoms or effects arising as a result of a treatment or a particular experiment, the design of the study is two groups pre test and post test design. Number of samples in this study were 23 samples with 12 samples in the treatment group and 11 in the control group samples were taken according to the inclusion criteria. Result: Statistical test in the specific training for agility on basketball player at SMAN 1 Kartasura showed p = 0.002, which means there is an influence from specific footwork training in improving agility possessed by basketball players at SMAN 1 Kartasura. The influence of different test in this study shows p = 0.00 <0.05, which means there is a difference between the treatment group and the control group. Conclusion: There was an effect of specific footwork training on agility for basketball players in SMAN 1 Kartasura Keywords: Agility, basket, specific footwork training